Correlation between sibling rivalry toward knowledge and development among preschool in kindergarten - Yektiningsih, Erwin; Firdausi, Nugrahaeni; Yuliansari, Pratiwi (Pediomaternal Nursing Journal, 2023)
Introduction: Preschool is the preoperational phase of the basics of significant mental and emotional development. Sibling rivalry and Parents' knowledge are essential in children's development. Sibling rivalry in preschool can be a problem because their unstable controlling emotion feels jealousy that influences mental effect activity and motivation toward concentration study impacts intellectual potency of the development stage, and can cause development failure.Methods: This study used a non-probability sampling technique with a cross-sectional approach. The population of this study consisted of 85 parents whose children attended Pembina Kindergarten Kediri for preschool and a sample of 30 parents was taken using purposive sampling. The sibling rivalry was an independent variable; the dependent variables were the level of knowledge and development. Data was gathered using a questionnaire tested for validity and reliability. The Indonesian Ministry of Health's Test Pra Screening Development (KPSP) Standard Questionnaire and Spearman-rho were employed in data analysis. Results: The study revealed a relationship between sibling rivalry level and knowledge (r=0.405, value =0.027) and development (r=0.722, value <0.001).Conclusions: Preschoolers should be given a nursing plan to help with the psychological components of developmentally stimulating them. So that preschool development continues to be at its best, early detection of developmental problems should be carried out. Keywords: development; knowledge; preschool; sibling rivalry